P450-mediated dehydrotyrosine formation during WS9326 biosynthesis proceeds via dehydrogenation of a specific acylated dipeptide substrate - Songya Zhang; Lin Zhang; Anja Greule; Julien Tailhades; Edward Marschall; Panward Prasongpholchai; Daniel J. Leng; Jingfan Zhang; Jing Zhu; Joe A. Kaczmarski; Ralf B. Schittenhelm; Oliver Einsle; et al. (Elsevier, 2023)
WS9326A is a peptide antibiotic containing a highly unusual N-methyl-E-2-3-dehydrotyrosine (NMet-Dht) residue that is incorporated during peptide assembly on a non-ribosomal peptide synthetase (NRPS). The cytochrome P450 encoded by sas16 (P450Sas) has been shown to be essential for the formation of the alkene moiety in NMet-Dht, but the timing and mechanism of the P450Sas-mediated α,β-dehydrogenation of Dht remained unclear. Here, we show that the substrate of P450Sas is the NRPS-associated peptidyl carrier protein (PCP)-bound dipeptide intermediate (Z)-2-pent-1'-enyl-cinnamoyl-Thr-N-Me-Tyr. We demonstrate that P450Sas-mediated incorporation of the double bond follows N-methylation of the Tyr by the N-methyl transferase domain found within the NRPS, and further that P450Sas appears to be specific for substrates containing the (Z)-2-pent-1'-enyl-cinnamoyl group. A crystal structure of P450Sas reveals differences between P450Sas and other P450s involved in the modification of NRPS-associated substrates, including the substitution of the canonical active site alcohol residue with a phenylalanine (F250), which in turn is critical to P450Sas activity and WS9326A biosynthesis. Together, our results suggest that P450Sas catalyses the direct dehydrogenation of the NRPS-bound dipeptide substrate, thus expanding the repertoire of P450 enzymes that can be used to produce biologically active peptides.